Reinsurance and financial performance of short term insurance companies in South Africa - Sognon, George Sermador (Graduate School of Business (GSB), 2019)
Profit driven companies have a responsibility to generate decent returns and pay dividends to their shareholders. Investors and shareholders of financial institutions are particularly concerned about their cash flow, risk and returns to ascertain the financial performance of the business. In the insurance industry, risk management and financial performance goes hand-in-hand. In order for the short-term insurance industry in South Africa to thrive, the right risk management policy is needed to keep the business afloat and make returns for shareholders and most importantly, effectively perform the risk indemnification function of meeting claim payment on the occurrence of specified losses. This research undertakes a study to understand the relationship between the use of reinsurance contracts by insurers as a risk management tool and its impact on financial performance of short-term insurance companies in South Africa. It employs data on 79 short-term insurers (2007 - 2014) sourced from the insurance department of the Financial Services Board (FSB). The random effect and fixed effect panel techniques are employed in this study to estimate both static panel data models to identify the determinants of financial performance for insurers. Return on assets (ROA), return on equity (ROE) and underwriting profit (UPROF) are employed as proxies of financial performance. The data analysis indicate that the average reinsurance ratio is 44% over the period of the study. The second-stage regression analysis showed that reinsurance contracts reduces profitability, which suggests that any potential risk diversification associated with reinsurance usage is offset by the loss of revenue in investment incomes. The findings also indicate that a negative relationship exist between underwriting risk and financial performance of short-term insurers. As underwriting risk exposure increases, insurers are expected to report lower profitability. The size of a short-term insurer correlates positively with financial performance. According to the findings, large insurance corporations in South Africa perform better than smaller sized insurers. As a result, mergers and acquisitions is the way-forward for the industry since consolidation positively impacts bottom-line due to economies of scale and capacity. The results from the findings also indicate that the use of leverage positively impacts financial performance of insurers as most insurers in South Africa are benefiting from reduced income tax payable due to interest payment to debt holders. A positive relationship exists between diversification of business lines and financial performance. The findings seem to suggest that diversified insurers increase gross premiums from the same client whiles reducing cost due to the scale of transactions. The findings from this study recommends that for short-term insurers to improve their financial performance, they will have to increase their retention ratio. This will lead to low reinsurance ratios allowing room for high net premiums to be available to the firm. While doing this, insurers have to be mindful of their risk management policies. Insurance companies also have to diversify their business lines, increase leverage and the asset size of the firm in order to increase profitability. The regulatory environment should be opened to reduced reinsurance ratios as long as risk management measures and enough capital are available to absorb risk in the future.